The effect of prognostic factors at baseline on the efficacy of trifluridine/tipiracil in patients with metastatic colorectal cancer: A Portuguese exploratory analysis - M.João de Sousa; Inês Gomes; Tatiana Cunha Pereira; Joana Magalhães; Raquel Basto; Judy Paulo; Paula Jacinto; Nuno Bonito; Gabriela Sousa (Cancer Treatment and Research Communications, 2022)
Background: The RECOURSE trial supported trifluridine/tipiracil as a treatment option in metastatic colorectal cancer (mCRC). Subsequent analysis demonstrated that low tumour burden and indolent disease are good prognosis factors improving progression-free survival (PFS) and overall survival (OS). This study aimed to evaluate the impact of prognosis group in the OS, PFS and safety of trifluridine/tipiracil in patients with mCRC. Methods: Single-centre, retrospective, and observational study of patients with mCRC who started trifluridine/tipiracil between February 2018 and July 2019. Patients were divided into good prognosis characteristics (GPC) [low tumour burden (less than 3 metastasis site) and indolent disease (≥18 months from first metastasis diagnosis)] and poor prognostic characteristics (PPC) group [high tumour burden (3 or more metastasis sites) and/or aggressive disease (<18 months since the first metastasis diagnosis)]. Results: Median age was 67 years (48–82), 67.3% of the patients were male, and 65.3% had stage IV disease at baseline. Overall, median OS was 7.5 months (95%CI:5.7–9.3). Twenty-two patients (44.9%) presented GPC and 29 (59.1%) had PPC. GPC patients had longer median OS [11.4 (95%CI:6.2–16.7)] versus 3.9 months [(95%CI: 3.3–4.6),p < 0.0001] and PFS [4.9 (95%CI:3.0–6.9) versus 2.6 months (95%CI:2.2–2.8),p < 0.0001]. These differences were more pronounced in GPC patients with no liver metastasis. Grade ≥3 adverse events incidence didn't vary between GPC and PPC subgroups. Conclusion: Our study validates the improved trifluridine/tipiracil efficacy in patients with GPC in comparison with PPC while maintaining a well-tolerated safety profile. Indolent disease, low tumour burden and the absence of liver metastasis were shown to be good prognosis factors influencing sustained response to trifluridine/tipiracil.